Blast off! - Loney, Andrea J. (Loney, Andrea J. Abby in orbit, 2022)
It is Abby Baxter's first day of third grade on the OASIS International Space Station and she is determined not to make any mistakes, but getting used to microgravity, watching her little brother, Nico, and meeting her new classmates, causes her to almost mess up Mami's big experiment.